2009
DOI: 10.1002/chem.200900962
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coherent Heteroclustering of Different Dyes by Use of Threoninol Nucleotides for Comparison with the Molecular Exciton Theory

Abstract: To test the molecular exciton theory for heterodimeric chromophores, various heterodimers and clusters, in which two different dyes were stacked alternately, were prepared by hybridizing two oligodeoxyribonucleotides (ODNs), each of which tethered a different dye on D-threoninol at the center of the strand. NMR analyses revealed that two different dyes from each strand were stacked antiparallel to each other in the duplex, and were located adjacent to the 5'-side of a natural nucleobase. The spectroscopic beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…This result suggests that the AzD is the much more efficient T-to-C photoisomerization molecule as a photoregulator compared to the already-reported Az 9 and its derivatives [3][4][5][6], with the advantage of the pump wavelength without damaging the living cell [7,8]. S -to-I T T C kinetic rate hardly changes.…”
Section: Azd Solutionmentioning
confidence: 87%
See 2 more Smart Citations
“…This result suggests that the AzD is the much more efficient T-to-C photoisomerization molecule as a photoregulator compared to the already-reported Az 9 and its derivatives [3][4][5][6], with the advantage of the pump wavelength without damaging the living cell [7,8]. S -to-I T T C kinetic rate hardly changes.…”
Section: Azd Solutionmentioning
confidence: 87%
“…[7]. The AzD solution in dimethylsulfoxide (DMSO, spectroscopic grade) was at the concentration of 4.0 mM or 8.0 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Although azobenzene derivatives are much larger than natural bases, they are stacked in antiparallel manner without disturbing natural base pairs ( Figure 2B). Thus, we concluded that surprisingly high stability of M-M pairs is caused by strong intermolecular stacking interactions between M residues.…”
Section: Methyl Red Pair Has High Stability and Orthogonalitymentioning
confidence: 99%
“…Although these isomers could be separated, the linker stereochemistry was difficult to assign with complete certainty. We therefore turned our attention towards a threoninol linker (Figure 1b), which has previously been successfully used in other studies on functionalised oligonucleotides 6,21,[24][25][26] and as an enantiopure starting material, removes the problem of generating diastereomers.…”
mentioning
confidence: 99%